2015
DOI: 10.1371/journal.pone.0144771
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Complications of Intercavernous Sinuses during Transsphenoidal Surgery: An Anatomical Analysis Based on Autopsy and Magnetic Resonance Venography

Abstract: PurposeVascular complications induced by intercavernous sinus injury during dural opening in the transsphenoidal surgery may contribute to incomplete tumour resections. Preoperative neuro-imaging is of crucial importance in planning surgical approach. The aim of this study is to correlate the microanatomy of intercavernous sinuses with its contrast-enhanced magnetic resonance venography (CE-MRV).MethodsEighteen human adult cadavers and 24 patients were examined based on autopsy and CE-MRV. Through dissection o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 33 publications
(28 reference statements)
0
21
0
Order By: Relevance
“…Similar to our study, others have reported variability in the presence of the sinuses, with the anterior being the most consistent of all (Table 2). [1][2][3][4]7,[9][10][11] Ridley is credited with the first description of the intercavernous sinuses in 1695, referring to them as the "circular sinus" given their configuration around the infundibulum 3,12 . In 1763, Winslow additionally recognized the inferior intercavernous sinus, which he termed the "inferior circular sinus."…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar to our study, others have reported variability in the presence of the sinuses, with the anterior being the most consistent of all (Table 2). [1][2][3][4]7,[9][10][11] Ridley is credited with the first description of the intercavernous sinuses in 1695, referring to them as the "circular sinus" given their configuration around the infundibulum 3,12 . In 1763, Winslow additionally recognized the inferior intercavernous sinus, which he termed the "inferior circular sinus."…”
Section: Discussionmentioning
confidence: 99%
“…1,11 It is found within the dura of the clivus, is generally multiloculated, and additionally communicates with the superior and inferior petrosal sinuses. 1 Some authors refer to a fifth "dorsum sellae sinus", which is a widened venous channel on the posterior aspect of the dorsum sellae, 9,20 but this nomenclature is inconsistent and others consider this to be part of the basilar sinus.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…MRV test results showed 13 samples of nonvisualized, from those 13 samples the angiography obtained 12 samples (92.3%) of thrombus, while the remaining sample was normal. Findings nonvisualized on MRV showed 92.3% of thrombus on its angiography cerebral could be due to the 3D-TOF flow gap occurs as a result of intravascular slow blood flow as blood flow patterns are complex and varied features 14 . This diversity illustrates the pathophysiological changes seen after venous occlusion.…”
Section: Discussionmentioning
confidence: 99%
“…It is a challenging procedure due to the complexity of the anatomical region and the limited surgical area [1,5]. Common complications include intercavernous sinus bleeding and internal carotid artery (ICA) laceration [6,9,13]. Part of the ICA is located inside the cavernous venous sinus until it passes through the dura mater that forms the roof of the venous sinus [7,28].…”
Section: Introductionmentioning
confidence: 99%